O COMPORTAMENTO DOS OBJETOS PÓSVERBAIS EM CONSTRUÇÕES APLICATIVAS DO CHANGANA - Clauâne Pâmela Leal Dias Carolino (2023)
Applicativization is a linguistic phenomenon in which an applied object is introduced into the verbal structure. This phenomenon is encoded by means of a lexical-functional category, the applicative head (Appl°), which can be realized morphologically by a suffix. The process of applicativization is commonly carried out in languages of the Bantu language group - which belongs to the Niger-Congo subfamily and the Congo-Kordofanian language family. This phenomenon can be observed in Changana, a Bantu language spoken in the southern region of Mozambique by about 1,919,217 speakers, according to INE (2017), being classified as S.53 by Guthrie (1967/71). The discussion proposed in the linguistic literature (Bresnan and Moshi, 1990; Pylkkänen, 2008) is that this process engages the insertion of an applied object (AO) that has distinct syntactic-semantic properties such as, for example, the possibility of being passivized or marked on the verb; the licensing of distinct thematic roles and the semantic relationship it maintains within the structure to which it is inserted. In light of Chomsky's (2001) and McGinnis' (2008) works and based on Changana data collected through a literature review of Chimbutane's (2002) work and by means of a questionnaire, the aim of this paper is to relate the different syntactic-semantic properties of postverbal objects to the proposal of derivation by phase, observing that there is a relationship between the syntactic derivation of applicative constructions and the syntactic-semantic behavior of applied and direct objects. The hypothesis I raise is that the Changana language data present a high applicative head that heads a phase so that in unmarked contexts this head does not trigger the edge-feature, EPP, making it impossible for the direct object to leave the VP level and generating asymmetric constructions. While in focused applicative constructions the applicative head has the EPP feature enabling the direct object to be focused or marked on the object and generating symmetric constructions. The justification of this paper is the intention of disseminating theoretical-descriptive work developed from the study of minority languages, since, although the Bantu languages are many and diverse, few theoretical-descriptive works are found in the linguistic literature.